PENERAPAN MODEL TERPADU DALAM PEMBELAJARAN MENULIS CERPEN ISLAMI - Emah Khuzaemah (Jurusan Tadris Bahasa Indonesia, 2016)
This research is motivated by the lack of a culture still writing among students. The ability to write literature students is still low. For that how to develop an integrated model of literary learning and its application to improve the writing skills of students. Thus the spiritual experience of students / students would be more meaningful if it is able to be expressed in a literary work. With a unified theoretical model developed by Fogarty (1991) and developed a theory of writing short stories integrated learning model in teaching writing short stories. Through a qualitative approach with descriptive analytic method, can be described Islami ability to write short stories high school students Kramat Dukupuntang after application of integrated learning model. Students' ability to write short stories Islami was satisfactory, catchy title, theme and content laden with religious values with storytelling techniques that have been organized.